Understanding psychotrauma in Sub-Saharan Africa: a scoping review of clinical and sociocultural perspectives - Cikuru, Justin; Kaganda, Philippe; Blavier, Adélaïde; Foucart, Jennifer (Frontiers in Psychology, 2025)
IntroductionSince independence, African states have faced armed conflicts and economic crises, disrupting traditional cultures and causing trauma. In Sub-Saharan Africa, psycho trauma is seen as a shared expression of distress rather than a medical condition. Understanding these cultural manifestations is crucial for evaluating Diagnostic and Statistical Manual of Mental Disorders (DSM-5) Posttraumatic stress disorder (PTSD) criteria. This review explores how PTSD symptoms manifest differently in these communities, aiming to enhance cultural understanding and improve patient care.MethodsWe conducted a double bind scoping review following the PRISMA guidelines. A systematic search was performed across multiple databases, including ScienceDirect, Cairn.info, SAGE Journals, Google Scholar, APA PsycInfo, Springer Link, PubMed, and ProQuest, for publications from 2016 to 2024 using the keywords PTSD, Sub-Saharan Africa, war trauma, sexual violence, culture, and expression of trauma.ResultsThe search returned 268 records. We identified 15 studies, written in English and French, that met the inclusion criteria. The studies were conducted in 8 countries Burkina Faso (n = 1) Cameroon (n = 2), Democratic Republic of the Congo (n = 4), Ivory coast (2), Kenya (1), Republic of Congo n = 1), South Africa (3) and Togo (n = 1). Nine studies (60%) highlight the symptoms related to PTSD showing that the DSM-5 emphasis psychological dimensions, whereas in sub-Sahara PTSD is primarily attributed to spiritual causes. Six studies (40%) highlight the meaning of symptoms in African anthropological structures, and the challenges faced by clinical psychologists in the context where mental health is not integrated in the cultural model of healing which involves spiritual rituals, traditional healers, and religious interventions.ConclusionThis scoping review underscores the necessity of a comprehensive understanding of PTSD in Sub-Saharan Africa, where trauma is predominantly expressed through somatic and spiritual frameworks. Recognizing these cultural expressions is essential for developing contextually relevant diagnostic approaches and improving culturally adapted patient care.